Pengaruh Profitabilitas, Ukuran Perusahaan, Leverage Resiko Perusahaan Terhadap Nilai Perusahaan - Danil Syahputra (Politeknik Kutaraja, 2020)
Research to analyze how much influence a profitability is the ability to get profit in a certain time, company size is a scale that describes and classifies how big or how small a company is in various ways, leverage or can be called the use of debt to see the value of a company and what risks a company has to the value of the company. The application and calculation of important risks in investing a company or can be referred to as an attempt by a company to maintain and enhance the value of a company, the authors take reference in making this research with previous studies so that in the future can be better development and evaluation again in getting company value.